The culture of patient safety in an emergency and emergency public hospital (Research, Society and Development, 2020)
Safety culture is the product of attitudes, skills and behavioral patterns, which are determinants in how professionals will adhere to health services, for maximum harm reduction and preventable risks. The objective of this research was to know the professionals' perception regarding the safety culture of the patient. An analytical cross-sectional study was conducted with patient care professionals. The questionnaire "Patient Safety Research in Hospitals" was applied. The dimensions with the highest positive response percentages were "Supervisor Expectations and Actions in Promoting Patient Safety," "Promotion and Continuous Learning," and "Teamwork in the Unit." Despite weaknesses, management's commitment to active actions to strengthen patient safety is noteworthy.